Azithromycin in the Management of Upper Respiratory Tract Infections (URTIs): Indian Real-Life Experience - Dominic M; Srivastava R; Shah K; Naik SM; Rout K; Ray B; Patil D; Rana D; Swami OC (Infection and Drug Resistance)
Mathew Dominic,1 Rakesh Srivastava,2 Kshitij Shah,3 Sudhir M Naik,4 Khageswar Rout,5 Bidhan Ray,6 Dinesh Patil,7 Darshan Rana,7 Onkar C Swami7 1Medical Trust Hospital, Ernakulam, 682016, Kerala, India; 2Raj ENT Centre and Voice Clinic, Lucknow, 226010, Uttar Pradesh, India; 3Criticare Asia Hospital, Mumbai, 400028, Maharashtra, India; 4The Oxford Medical College and Research Hospital, Bangalore, 562107, Karnataka, India; 5LASER ENT Clinic, Bhubaneswar, 751021, Orissa, India; 6IIMSAR & Dr. BC Roy Hospital, Haldia, 721631, West Bengal, India; 7Alembic Pharmaceuticals Limited, Mumbai, Maharashtra, 400099, IndiaCorrespondence: Onkar C Swami, Alembic Pharmaceuticals Limited, Mumbai, 400099, Maharashtra, India, Tel +91 9372423101, Email onkar.swami@alembic.co.inObjective: Upper Respiratory Tract Infections (URTIs) pose a significant public health challenge worldwide. Azithromycin has been approved for its management due to broad-spectrum antibacterial properties and favorable pharmacokinetics. This study aims to evaluate the effectiveness and safety of Azithromycin in treatment of URTIs in a real-world setting.Methods: This multicenter, retrospective, observational study was conducted across 184 Ear, Nose, and Throat (ENT) clinics in India. Medical records of adults (≥ 18 years) who received Azithromycin 500 mg for 5 days to treat URTIs and provided consent were retrieved. Sore throat, fever, and interference with daily activities were assessed alongside clinical signs (pharyngeal erythema, tonsillar erythema, and exudates/plugs on tonsils). Clinical global impression of change was evaluated using a 7-point rating scale. Statistical analyses included paired t-tests for mean score changes and the McNemar–Bowker test to evaluate symptom improvement from baseline to day 5.Results: Data from 884 patients were analyzed. With 5 days of Azithromycin therapy, significant reduction in proportion of patients reporting URTI symptoms and signs was noted. Proportion of patients reporting sore throat was reduced from 95.8% to 10.4%; work absenteeism dropped from 47.9% to 1%; and fever subsided in 97.4% of patients. Clinical signs also improved notably, with moderate-to-severe pharyngeal erythema (90.9% of patients at baseline to 13.6% at day 5), tonsillar erythema (84% of patients at baseline to 9.6%), and tonsillar exudates (58.3% patients at baseline to 4.4%). Also, 97.2% of patients showed considerable improvement in their Clinical Global Impression score with Azithromycin. Adverse events were reported by 2.37% of patients.Conclusion: Azithromycin demonstrates a significant improvement in clinical manifestations of URTIs, with a low incidence of adverse events.Keywords: Azithromycin, Upper Respiratory Tract Infections (URTIs), URTIs, sore throat, pharyngeal erythema, tonsillar erythema, India